Die with zero : getting all you can from your money and your life - Perkins, Bill (William O.), 1969- (Boston : Houghton Mifflin Harcourt, 2020)
A new philosophy and practical guide to getting the most out of your money-and out of life-for those who value memorable experiences as much as their earnings.
Optimize your life -- Invest in experiences -- Why die with zero? -- How to spend your money (without actually hitting zero before you die) -- What about the kids? -- Balance your life -- Start to time-bucket your life -- Know your peak -- Be bold -- not foolish.
Includes bibliographical references and index.
Keywords: Finance, Personal; Wealth -- Psychological aspects; Satisfaction; Self-help publications